Somatic development and some motor performances of young girls based on age and birth season - Szabó, Eszter; Keczeli, Danica; Farmosi, István; Gaál, Sándorné; Keresztesi, Katalin (Applied Studies in Agribusiness and Commerce, 2013)
There are numerous publications in the literature reporting physical development and motor performances of children of different ages based on sex and various environmental factors. However, there are not many publications on the birth season effect. The aim of the study was to evaluate the differences among children in physical development and motor performances based on age and birth season. Physical development described by body height and body weight, in addition to motor performance indicators including the twenty-metre dash, standing broad jump, six minutes of continuous running, throwing with a stuffed ball, and obstacle race-tests were studied. The survey included the participation of 426 girls. From the group the seven-, eight-, and nine-year olds numbered 148, 191, and 87 respectively. The group of girls who were born in winter, spring, summer and autumn numbered 114, 110, 89 and119 respectively. The tested data were evaluated with unitrate analyses of variance using SPSS statistical package. Mean value, standard error, standard deviation and coefficient of variation were calculated. The significance of differences between mean values was evaluated using “t” test. Differences with an error below 5% were considered to be significant. Furthermore, a correlation analysis was used to evaluate the relationship between season of birth, body development and motor-related performance data. Age, body height, body weight, throwing a stuffed ball in one hand, twenty-metre dash, six minutes of continuous running, and obstacle race-test are interdependent variables of development and motor performances of young girls of this age. Data from the study results show that the children group included in the tests was quite homogenous in body height, but heterogeneous in body weight and motor performances. Physical development and four of the five evaluated sport skills were affected by the birth season. Development and motor performances of the summer- and autumn-born girls are generally better than those born in winter or spring. Differences are significant except for the obstacle race-test. Age, body height, body weight, throwing with a stuffed ball in one hand, twentymetre dash, six minutes of continuous running, and the obstacle race-test seem to be interdependent variables of development and motor performances of young girls of this age.